Major morbidity after lung resection: a comparison between the European Society of Thoracic Surgeons Database system and the Thoracic Morbidity and Mortality system - Salati, Michele; Refai, Majed; Pompili, Cecilia; Xiumè, Francesco; Sabbatini, Armando; Brunelli, Alessandro (Journal of Thoracic Disease, 2013)
Objective: The Thoracic Morbidity and Mortality (TM&M) classification system is a method for univocally coding the postoperative adverse events by their complexity of management. The aim of the present study was to compare the distribution of the severity of complications according to the TM&M system versus the distribution according to the classification proposed by European Society of Thoracic Surgeons (ESTS) Database in a population of patients submitted to lung resection in our unit. Methods: 457 patients with any type of complications (326 lobectomy, 60 pneumonectomy, 71 wedge/segmentectomy) out of 1,518 patients submitted to pulmonary resections (January 2000-April 2011) were analyzed. Each complication was graded from I to V (TM&M system), reflecting an increasing severity of management. We verified the distribution of the different grades of complications and analyzed their frequency among those defined as “major cardio-pulmonary complications” by the ESTS Database. Results: According to the TM&M system, 0.6% of complications were regarded as grade I, 66.3% as grade II, 9.5% as grade IIIa, 4.4% as grade IIIb, 6.8% as grade IVa, 3.3% as grade IVb and 9.1% as grade V. According to the ESTS definitions, 290 complications were regarded as “major”. Sixty two percent of them were reclassified as minor complications (grade I or II) by the TM&M classification system. Conclusions: The application of the TM&M grading system questions the traditional classification of complications following lung resection. This grading system may be used as an additional endpoint for outcome analyses.